Role of B800 in carotenoid-bacteriochlorophyll energy and electron transfer in LH2 complexes from the purple bacterium Rhodobacter sphaeroides - Polívka, Tomas; Niedzwiedzki, Dariusz; Fuciman, Marcel; Sundström, Villy; Frank, Harry A (The journal of physical chemistry. B, 2007)
The role of the B800 in energy and electron transfer in LH2 complexes has been studied using femtosecond time-resolved transient absorption spectroscopy. The B800 site was perturbed by application of lithium dodecyl sulfate (LDS), and comparison of treated and untreated LH2 complexes from Rhodobacter sphaeroides incorporating carotenoids neurosporene, spheroidene, and spheroidenone was used to explore the role of B800 in carotenoid to bacteriochlorophyll-a (BChla) energy transfer and carotenoid radical formation. Efficiencies of the S1-mediated energy transfer in the LDS-treated complexes were 86, 61, and 57% in the LH2 complexes containing neurosporene, spheroidene, and spheroidenone, respectively. Analysis of the carotenoid S1 lifetimes in solution, LDS-treated, and untreated LH2 complexes allowed determination of B800/B850 branching ratio in the S1-mediated energy transfer. It is shown that B800 is a major acceptor, as approximately 60% of the energy from the carotenoid S1 state is accepted by B800. This value is nearly independent of conjugation length of the carotenoid. In addition to its role in energy transfer, the B800 BChla is the only electron acceptor in the event of charge separation between carotenoid and BChla in LH2 complexes, which is demonstrated by prevention of carotenoid radical formation in the LDS-treated LH2 complexes. In the untreated complexes containing neurosporene and spheroidene, the carotenoid radical is formed with a time constant of 300-400 fs. Application of different excitation wavelengths and intensity dependence of the carotenoid radical formation showed that the carotenoid radical can be formed only after excitation of the S2 state of carotenoid, although the S2 state itself is not a precursor of the charge-separated state. Instead, either a hot S1 state or a charge-transfer state lying between S2 and S1 states of the carotenoid are discussed as potential precursors of the charge-separated state.
Keywords: Spectrum Analysis; bakteriální proteiny; Electrons; bakteriochlorofyly; Electron Transport; elektrony; kinetika; Light-Harvesting Protein Complexes; transport elektronů; světlosběrné proteinové komplexy; Rhodobacter sphaeroides; Carotenoids; Bacteriochlorophylls; Bacterial Proteins; Kinetics; spektrální analýza; karotenoidy